What we could have learned from the New Deal in confronting the recent global recession - Jan A. Kregel (Levy Economics Institute of Bard College, 2016)
To the extent that policymakers have learned anything at all from the Great Depression and the policy responses of the 1930s, the lessons appear to have been the wrong ones. In this public policy brief, Director of Research Jan Kregel explains why there is still a great deal we have to learn from the New Deal. He illuminates one of the New Deal's principal objectives - quelling the fear and uncertainty of mass unemployment - and the pragmatic, experimental process through which the tool for achieving this objective - directed government expenditure - came to be embraced. In the search for a blueprint from the 1930s, Kregel suggests that too much attention has been paid to the measures deployed to shore up the banking system, and that the approaches underlying the emergency financial policy measures of the recent period and those of the 1930s were actually quite similar. The more meaningful divergence between the 1930s and the post-2008 policy response, he argues, can be uncovered by comparing the actions that were taken (or not taken, as the case may be) to address the real sector of the economy following the resolution of the respective financial crises.
Keywords: 330